18F-FAZA PET imaging in tumor hypoxia: A focus on high-grade glioma. Issue 1 (February 2020) - Mapelli, Paola; Picchio, Maria
The presence of hypoxia is a typical feature of solid tumors and has been identified in many neoplasms, favouring the survival of malignant cells in a hostile environment and the expression of an aggressive phenotype. Malignant brain tumors have large proportions of hypoxic tissue, thus contributing to resistance to radiation and chemotherapy. Positron emission tomography (PET) is an attractive technique to gain a non-invasive assessment of tumor hypoxia within the whole tumor, with 18F-fluoromisonidazole (18F-FMISO) and 18F-flouroazomycin arabinoside (18F-FAZA) being the most promising radiotracers. In this short review, we aim to discuss the available clinical studies focused on the use of 18F-FAZA PET/computed tomography in patients affected by high-grade glioma.